Aspectos da performance em Copacabana mon amour: entre o ator e a mise en scène no cinema de Rogério Sganzerla - Oliveira, Karine Matos de (2021)
This research has as its theme the acting in modern Brazilian cinema, focusing on Rogério Sganzerla's cinema in the context of Cinema Marginal that emerged in the second half of the 1960s. The corpus of the research consists of the film Copacabana mon amour (1970), directed by Sganzerla when he worked at the production company Belair. The objective of the research is to apply the concept of performance in a study of cinematographic stylistics focused on the mise en scène, emphasizing the work of the actors, in order to understand to what extent Copacabana mon amour incorporated elements characteristic of the performance as an artistic language, defining, thus, its particularities as a film of modern Brazilian cinema. The hypothesis is that Rogério Sganzerla adopted forms in the film Copacabana mon amour that have aspects in common with the way of thinking and making the scene, as well as the way of being in the scene of performance art. The language of the performance is taken as a type of scenic expression that has its own ways of acting and construction of the scene and that emphasizes the event at the moment of its presentation. Therefore, the cinema made by Sganzerla in Belair goes against a way of disposing the mise en scène approached by Aumont (2008a) and Oliveira Júnior (2013), which emerged in modern cinema, which values the creation of the actor at the time of filming as a component of its composition. This is a qualitative study that uses film analysis as a methodology. The result achieved with the research is that by combining aspects of the language of performance with an approximation of reality through the scenarios typical of modern cinema, Sganzerla allowed the actors to perform similar to that performed in performance art.